2023
DOI: 10.3390/act12020081
|View full text |Cite
|
Sign up to set email alerts
|

Design of Farm Irrigation Control System Based on the Composite Controller

Abstract: Farmland irrigation is an essential foundation for good crop growth, while traditional farmland irrigation techniques cannot fully consider the impact of factors such as natural precipitation and crop transpiration on crop growth, which can, to a certain extent, result in poor irrigation decisions and a complex farmland environment that cannot be monitored promptly, thereby reducing farmland production efficiency. This study designs a farmland irrigation control system based on a composite controller. Firstly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Along this line, other authors have indicated that the water requirements for several crops can be sufficiently modeled for the considered climate based on virtual sensors and fuzzy logic control systems [7,8]. Li et al [9] proposed a composite irrigation controller that considers predictive algorithms, crop coefficients, fuzzy algorithms, and sliding mode control methods for maize irrigation scheduling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along this line, other authors have indicated that the water requirements for several crops can be sufficiently modeled for the considered climate based on virtual sensors and fuzzy logic control systems [7,8]. Li et al [9] proposed a composite irrigation controller that considers predictive algorithms, crop coefficients, fuzzy algorithms, and sliding mode control methods for maize irrigation scheduling.…”
Section: Introductionmentioning
confidence: 99%
“…Their simplicity and high degree of adaptation at the farm level, which are characteristics of the evaporation pan, seem to be the primary reason for the pan's expansion among producers. The work of Thomson and Fisher (2006) [9], who designed an evaporimeter based on a washtub for easy cotton irrigation scheduling, is relevant. Similarly, other researchers have proposed activating a drip irrigation system based on a water level sensing system in a mini-pan [18].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the availability of real-time control of farm equipment through automated actuation devices, such as feeders, seed drills, valve-controlled irrigation systems, etc., in the market, there has been limited progress in the development of wireless technologies for transferring sensor data wirelessly from crop fields to remote servers [6,21]. Besides that, agriculture has become more complex, and farmers cannot rely solely on traditional farming methods to improve their yields and profits [7].…”
Section: Introductionmentioning
confidence: 99%